biofuel of plants for the production of biodiesel - Calvo B., Eduardo (2006)
Biofuels have accompanied mankind since the discovery of fire use. The development of modern agriculture (Green revolution, Biotechnology and microorganism symbioses) allows us to give a fresh look to the possibilities of raising our future fuel. In this paper, an overview of the potencial of different plant natural reources in Peru and their application perspective is presented.